2002
DOI: 10.1021/ja0261731
|View full text |Cite
|
Sign up to set email alerts
|

5-Endo-trig Radical Cyclizations:  Disfavored or Favored Processes?

Abstract: Relative kinetic data were determined for the 5-endo-trig cyclization of radical 12 compared to hydrogen abstraction from (TMS)(3)SiH in the temperature range of 344-430 K, which allows for the estimation of a rate constant of 2 x 10(4) s(-)(1) at 298 K with an activation energy of ca. 9 kcal/mol for the cyclization process. The 5-endo-trig cyclization of a variety of radicals that afford five-membered nitrogen-containing heterocycles was addressed computationally at the UB3LYP/6-31G level. The 5-endo vs 4-exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 54 publications
2
59
1
3
Order By: Relevance
“…This notion is supported by the NBO analysis that reveals a strong donation from the lone pair at N1–C5 at the TS: the E(2) donor–acceptor interaction is 84.2 kcal/mol for TS‐ trans and 103.8 kcal/mol for TS‐ cis , respectively. This scenario would resemble a 5‐ endo ‐trig reaction which is assumed to be disfavored according to Baldwin's rules, which are, however, only qualitative and may be less reliable for systems containing heteroatoms . Recently, Johnston et al demonstrated that also all‐carbon systems may preferentially cyclize in a 5‐ endo ‐trig manner .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is supported by the NBO analysis that reveals a strong donation from the lone pair at N1–C5 at the TS: the E(2) donor–acceptor interaction is 84.2 kcal/mol for TS‐ trans and 103.8 kcal/mol for TS‐ cis , respectively. This scenario would resemble a 5‐ endo ‐trig reaction which is assumed to be disfavored according to Baldwin's rules, which are, however, only qualitative and may be less reliable for systems containing heteroatoms . Recently, Johnston et al demonstrated that also all‐carbon systems may preferentially cyclize in a 5‐ endo ‐trig manner .…”
Section: Discussionmentioning
confidence: 99%
“…This scenario would resemble a 5-endo-trig reaction which is assumed to be disfavored according to Baldwin's rules, [33] which are, however, only qualitative and may be less reliable for systems containing heteroatoms. [34][35][36][37] Recently, Johnston et al demonstrated that also all-carbon systems may preferentially cyclize in a 5-endotrig manner. [38] They probed by DFT computations whether an electrocyclization is reasonable but had to exclude this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016 Clark and co‐workers reported a fruitful method for achieving four‐membered lactams based on a Cu(0) (copper wire)‐mediated stereoelectronically favored 4‐ exo‐trig ring closure of the unsaturated α‐bromo amide A (Scheme ).…”
Section: Intramolecular α‐Alkylation Of α‐Haloamides: Syntheses Of β‐mentioning
confidence: 99%
“…In a multichannels reaction, there are two or more major products in general. It is always thought that if there is no selectivity in the initially divergent step, the overall reaction will not be selective . As illustrated in Scheme , when two diastereotopic groups X and X′ exist in the precursor, they will convert into different substituents A and B in the initially divergent step.…”
Section: Introductionmentioning
confidence: 99%